PEMANFAATAN APLIKASI INSTAGRAM SEBAGAI MEDIA PENUNJANG CYBER COUNSELING ISLAMI - Ilmiyati Refi Fadlia; Ahmad Fauzi (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2024)
Technological advances make it easier for us to carry out various activities. This also includes the implementation of counseling. The use of Instagram as a supporting medium for Islamic cyber counseling found in the Instagram account @muhammadnuzuldzikri. The aim of this research is to find out how to analyze the use of Instagram as a supporting media in cyber counseling. The research method used in this research is the qualitative research method of content analysis. This research uses content analysis research. The type of data used in this research is photo and video content on @muhammadnuzuldzikri's Instagram. The data sources used are data obtained or collected and then combined. The data collection technique in this research consists of three units, namely the sample unit is part of the selected object, namely in the form of photos and videos. The data analysis used in this research is content analysis techniques. The results of this research show that Instagram is quite effective as a media to support cyber counseling. The uploaded posts have Islamic counseling values such as family values, establishing good relationships with people, mental therapy, gratitude therapy, patient therapy and good ethics with other people. The value of Islamic education on Instagram as a supporting medium for Islamic cyber counseling is in the form of lessons and teaching to clients and counselors, always maintaining the spirit and soul because it has a big influence on a person's happiness and is accompanied by getting closer to Allah and the Koran.